Complications in blepharoplasty: how to avoid and manage them Complicações em blefaroplastia: como evitá-las e corrigi-las - Tomas Gomes Patrocinio; Bruno Alvarenga Silva Loredo; Carlos Eduardo Arnez Arevalo; Lucas Gomes Patrocinio; José Antonio Patrocinio (Brazilian Journal of Otorhinolaryngology, 2011)
Complications in blepharoplasty are uncommon and, when they occur, they are usually mild and transient, such as hematomas and chemosis. However, sometimes they can be severe, such as blindness, or they might require surgical correction, such as ectropion. OBJECTIVE: To evaluate the results and complications of transcutaneous blepharoplasty performed in the same procedure, discussing how to treat and how to avoid them. METHODS: A retrospective study of 200 medical records of consecutive patients that underwent transcutaneous blepharoplasty from January 2007 to January 2009. The variables analyzed were age, gender, complications, clinical outcome, patient satisfaction, and photographic documentation. RESULTS: The incidence of complications was 9.5% (19 patients). The complications were 1 hematoma, 12 cases of chemosis and 13 patients who underwent canthoplasty, 6 patients with malposition of the lower eyelid (5 retractions and 1 ectropion). Medical treatment was performed in 12 patients and revision surgery in 7 cases of all the patients who had complications. CONCLUSIONS: We demonstrated that blepharoplasty is a procedure with a high satisfaction and a low complication rate, and it is an excellent surgical procedure, when properly indicated. As complicações em blefaroplastia não são comuns e quando ocorrem são geralmente discretas e transitórias, como hematoma e quemose. Entretanto, algumas vezes podem ser definitivas, como cegueira, ou necessitarem de novas abordagens cirúrgicas para correção, como ectrópio. OBJETIVO: Avaliar resultados e complicações das blefaroplastias transcutâneas realizadas em um mesmo serviço, demonstrando como tratá-las e evitá-las. CASUÍSTICA E MÉTODO: Estudo retrospectivo de 200 prontuários de pacientes consecutivos submetidos à blefaroplastia transcutânea entre o período de janeiro de 2007 a janeiro de 2009 em um mesmo serviço. As variáveis analisadas foram: idade, sexo, complicações, evolução clínica, grau de satisfação e documentação fotográfica. RESULTADOS: A incidência de complicações foi de 9,5% (19 pacientes). As complicações encontradas foram: 1 hematoma, 12 casos de quemose, sendo que esta ocorreu em 61,5% dos 13 pacientes que realizaram cantoplastia, 6 pacientes com mau posicionamento de pálpebra inferior, sendo que, destes, 5 correspondem à retração e 1 ao ectrópio. Foi realizado tratamento clínico com acompanhamento ambulatorial em 12 pacientes e cirurgia revisional em 7 casos do total de pacientes com complicações. CONCLUSÕES: Demonstrou-se que a blefaroplastia é uma cirurgia com alta taxa de satisfação e baixo número de complicações, sendo um excelente procedimento cirúrgico, quando corretamente indicada.